Cultural resource overview : Aboriginal sites in the Northern Region, NSW - a report to the National Parks & Wildlife Service (NSW) - Byrne, Denis (Denis Richard), 1949-; New South Wales. National Parks and Wildlife Service ([S.l. : s.n.], 1989)
Compilation and summary of archaeological sites in the north-east region of NSW; site types by region - brief overviews and discussion of middens, burials, rockshelters, open sites, stone sources, quarries, ochre sources, axe-grinding groves, scarred trees; rock art sites; sites of religious and mythological significance - Bora grounds, stone arrangements, carved trees; post-contact sites - massacre sites, missions, reserves; assessment of resource condition; management issues; recommendations.
Cover title.
Includes bibliographical references.
Keywords: Aboriginal Australians -- New South Wales -- Northern Region -- Antiquities; Historic sites -- New South Wales -- Northern Region; Sites - Surveys; Cultural heritage - Management; Northern Region (N.S.W.) -- Antiquities; Northern New South Wales (N NSW SH55, SH56)